Corruption in Village Governments: A Bibliometric Review and Future Research Agenda (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This study aims to review the village over forty-two years of village corruption spanning 1980 to 2022 to provide a broad overview of the literature and propose a future research agenda. Design/Methodology/Approach: The study analyzed 155 articles from the Scopus database utilizing VOSviewer software. Research findings: The findings exhibited that the studies in this area have increased significantly in the last two decades, with the United States of America emerging as the predominant contributor in this area of study. The other interesting finding is that the research focus has evolved from economics to non-economics. This study, hence, proposes that technology implementation in village government is a crucial topic to be analyzed to enhance the village corruption literature and to decrease and detect corruption at the village level. Theoretical contribution/Originality: This study contributes to synthesizing current and upcoming research trends and offers recommendations for future research direction in the village corruption study.